Development of microwave-stabilized rice bran application in emulsified products - Ayende, Hunny Padua (UP College of Home Economics, 2012)
This study aimed to use microwave stabilized rice bran (SRB) as an ingredient in pasteurized emulsion-based meat batter using the formulation of the Bureau of Animal Industry (BAI) at 2.5% and 5% levels of incorporation. The functional properties of the SRB, including: bulk density (BD); water holding capacity (WHC); fat absorption capacity (FAC); emulsification capacity (EC); and foaming capacity (FC) increased with the microwave stabilization. The process, however, decreased emulsion stability (ES). The SRB was found to have a higher affinity for water than fat. Functional properties of raw meat batters showed that increasing levels of microwave SRB improved WHC and ES values, while fat separation significantly increased at 5% level of incorporation. Increased hydrophobicity of the SRB was noted after microwave stabilization. Increased WHC and ES of the meat batters with SRB were based on the inherent high WHC of SRB as a result of possible physical entrapment and binding of liquids by SRB. Increased incorporation up to 5% microwave SRB likewise decreased material costs by about Php3/kg of the meat batters. Incorporation of SRB did not significantly affect the water activity, moisture content, and pH of pasteurized meat batters as hotdogs, while ES and gel firmness values of pasteurized hotdogs decreased. Increased hardness with decrease in gel firmness of pasteurized hotdogs may be due to the ability of the SRB to develop structural integrity by entrapping water in the meat batter. The microbial profile of microwave SRB is as follows: 105 cfu/g Total Plate Count (TPC), 102-104 cfu/g Yeast and Mold Count (YMC) , and <3.0 MPN index/g Total Coliform. Pasteurized meat batters as hotdogs with 2.5% to 5% incorporation showed TPC and YMC of 104. Incorporation of SRB up to 5% decreased Total Coliform from 4.5 of control to <3.0 MPN index/g. The vii pasteurized meat batter as hotdog with 2.5% SRB has the highest over-all acceptability compared to control and hotdog with 5% SRB incorporation. It was recommended that rice bran samples be subjected to defatting before microwave stabilization to further increase its functional properties. The incorporation of 2.5% full-fat SRB can already be recommended for commercial production. This study was conducted as part of a University of the Philippines, College of Home Economics-Philippine Council for Industry, Energy and Emerging Technology Research and Development-Department of Science and Technology research project entitled: Stabilization of Rice Bran Using Microwave Volumetric Heating for Emulsion-Based Processed Meat.